2016
DOI: 10.1111/cch.12386
|View full text |Cite
|
Sign up to set email alerts
|

Positional plagiocephaly reduces parental adherence to SIDS Guidelines and inundates the health system

Abstract: There is a need to re-emphasize sudden infant death syndrome guidelines for families when they present with an infant with plagiocephaly. Stronger messaging regarding the lack of safety of current pillows marketed to prevent flat head may be useful to decrease their use. Increasing education for all health professionals including general practitioners, allied health and complementary health providers and standardizing assessment and referral criteria may allow the majority of diagnosis and treatment of positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 15 publications
0
44
1
1
Order By: Relevance
“…In a recent review, most of the studies reviewed revealed an association between PPB and developmental outcomes. 8 Aside from the Miller and Clarren 7 study, nearly all of this research involved infants and toddlers.…”
mentioning
confidence: 99%
“…In a recent review, most of the studies reviewed revealed an association between PPB and developmental outcomes. 8 Aside from the Miller and Clarren 7 study, nearly all of this research involved infants and toddlers.…”
mentioning
confidence: 99%
“…[16] In a recent review paper, 13 of 19 studies reviewed reported developmental delays among infants with PPB. In children < 2 years of age, motor skills were the most commonly affected domain.…”
mentioning
confidence: 99%
“…This is not surprising given the known link between skull deformation and limitations in head and neck movement (e.g., torticollis), and associations between skull deformation and environmental restrictions on movement (e.g., consistent sleep positioning, limited ‘tummy time’). [16]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a qualitative study using focus group discussion and semi‐structured interviews in Australia, parents’ views of NSP prevention were examined. (Martiniuk, Jacob, Faruqui, & Yu, ). The researchers reported that some parents were more concerned about preventing NSP than SIDS because NSP was more of a reality.…”
Section: Discussionmentioning
confidence: 99%